Gender Codes of Shame and Guilt: Correlations and Consequences on the Part of Nazi Perpetrators and Their Descendants (KULT_online, 2012)
Avowals of shame and guilt play a major role in contemporary discourses of remembrances of national socialist crimes. Furthermore, they represent an extensive interpretation pool of German guilt (cf. p. 9). For the differentiation of this pool, the interdisciplinary anthology Scham und Schuld. Geschlechter(sub)texte der Shoah (Shame and Guilt. Gender (Sub)Texts of the Shoah) published by Maja Figge, Konstanze Hanitzsch, and Nadine Teuber discusses whether shame and guilt have been disseminated to the second and third generations of NS perpetrators, as well as the significance of these emotions in the remembrance of and political debate about national socialist crimes (cf. p. 9). Therefore, it is the subtexts of avowals of shame and guilt that dominate in all 14 articles. Despite the diversity of perspectives the premise is proved that a specific gender codification of shame and guilt provokes a discharge, a cover up, and a mystification of the Shoah (cf. p. 10).